Analisis Yuridis Omnibus Law dalam Penyusunan Rancangan Undang-undang Cipta Kerja - I Kadek Semara Atmika; I Nyoman Budiartha; lda Ayu Putu Widiati (Warmadewa Press, 2021)
Indonesia is a country that adheres to the civil law system, many regulations from central to regional. As a result, many laws and regulations overlap in both vertical and horizontal directions. To organize overlapping regulations, coordination must be done. The concept of comprehensive law has been successfully applied in most countries that adhere to the common law system, but Indonesia that adheres to the civil law systern is still unfamiliar with the term. Therefore, the goals of this research are to analyze the comprehensive legal position in the preparation of Indonesian law and to discuss comprehensive law applied in the law of job creation. This research is normative legal research, used statutory approach and conceptual approach. The results show that the status and application of comprehensive law is v’ery imponant for the development of the law to enforce legal certainty. The formulation of legislation with a comprehensive legal concept requires in-depth research, and for the sake of transparency in the formatinn of many political parties involved, so as nnt to cause problems and harm the public interest, especially the social interest.